The problem of misidentification between edible and poisonous wild plants: Reports from the Mediterranean area. (September 2018) - Cornara, L.; Smeriglio, A.; Frigerio, J.; Labra, M.; Di Gristina, E.; Denaro, M.; Mora, E.; Trombetta, D.
Abstract: Today, in many European countries, people are looking for wild edible plants to experience new tastes and flavors, by following the new trend of being green and environmentally friendly. Young borage and spinach leaves can be easily confused by inexpert pickers with those of other plants, including poisonous ones, such as Mandragora autumnalis Bertol. (mandrake) or Digitalis purpurea L. (foxglove), common in southern and northern Italy respectively. In the last twenty years, several cases of intoxication by accidental ingestion of mandrake and foxglove have been reported. The purpose of this work was to perform a pharmacognostic characterization of young leaves from borage, mandrake, foxglove and spinach, by micro-morphological, molecular and phytochemical techniques. The results showed that each of the three techniques investigated could be sufficient alone to provide useful information for the identification of poisonous species helping the medical staff to manage quickly the poisoned patients. However, the multi-disciplinary approach proposed could be very useful to asses the presence of poisonous plants in complex matrices, to build a database containing morphological, molecular and phytochemical data for the identification of poisonous species or in forensic toxicology, given their increasingly frequent use due to their low cost and relatively common availability. Graphical abstract: Highlights: The problem of misidentification between edible and poisonous wild plants. The analysis of leaf fragments by light microscope is useful to identify the species. DNA analysis confirms the possibility of distinguishing all the species, due to the high genetic interspecific variability. The phytochemical screening revealed a typical chemical fingerprint of each plant analysed. The analysis carried out provide useful information for the identification of the poisonous species.